How can patient preferences be used and communicated in the regulatory evaluation of medicinal products? Findings and recommendations from IMI PREFER and call to action - Janssens, Rosanne; Barbier, Liese; Muller, Mireille; Cleemput, Irina; Stoeckert, Isabelle; Whichello, Chiara; Levitan, Bennett; Hammad, Tarek A.; Girvalaki, Charis; Ventura, Juan-Jose; Bywall, Karin Schölin; Pinto, Cathy Anne; et al. (Frontiers in Pharmacology, 2023)
Objective: Patients have unique insights and are (in-)directly affected by each decision taken throughout the life cycle of treatments. Patient preference studies (PPS) assess what matters most to patients, how much, and what trade-offs patients are willing to make. IMI PREFER was a six-year European public-private partnership under the Innovative Medicines Initiative that developed recommendations on the assessment and use PPS in medical product decision-making, including in the regulatory evaluation of medicinal products. This paper aims to summarise findings and recommendations from IMI PREFER regarding i) PPS applications in regulatory evaluation, ii) when and how to consult with regulators on PPS, iii) how to reflect PPS in regulatory communication and iv) barriers and open questions for PPS in regulatory decision-making.Methods: PREFER performed six literature reviews, 143 interviews and eight focus group discussions with regulators, patient representatives, industry representatives, HTA bodies, payers, and clinicians.Results: (i) Regarding PPS applications, during the evaluation of a marketing authorization application, PPS could inform whether patient-relevant clinical trial endpoints were included and the understanding of patient-relevant effect sizes and acceptable trade-offs. (ii) Regarding consulting with regulators on PPS, PPS researchers should ideally have early discussions with regulators (e.g., during scientific advice) on the PPS design and research questions. (iii) Regarding external PPS communication, PPS could be reflected in the regulatory assessment report and product information. (iv) Barriers for use of PPS in regulatory evaluation include a lack of demonstrated impact of PPS on regulatory decisionmaking, and need for incentives, guidance and quality criteria for PPS. Questions concerning regulatory PPS use include: a) should a product independent broad approach to the design of PPS be taken and/or a product-specific one, b) who should optimally be financing, designing, conducting, and coordinating PPS, c) when (within and/or outside clinical trials) to perform PPS, and d) how can PPS use best be operationalised in regulatory decisions. Conclusion: PPS have high potential to inform regulators on key benefits and risks that matter most to patients and their acceptable trade-offs. Regulatory guidelines, templates, checklists, and incentives are needed to foster structural and transparent PPS submission and evaluation in regulatory decision-making.